CHILD-FRIENDLY SCHOOL MANAGEMENT AND BULLYING PREVENTION: A QUANTITATIVE CASE STUDY FROM AN INDONESIAN PUBLIC ELEMENTARY SCHOOL - Shanti Cahyani; Yovitha Yuliejantiningsih; Muhammad Prayito (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Bullying in elementary schools continues to be a significant concern, negatively impacting students' emotional well-being, social interactions, and academic engagement. In response, many schools in Indonesia have adopted the Child-Friendly School (CFS) program as a strategic initiative to foster a safe and inclusive learning environment. SDN Pleburan 01 Semarang is one such school dedicated to strengthening bullying prevention through effective child-friendly school management strategies. This study aims to analyze the approaches employed by SDN Pleburan 01 in managing a child-friendly school to prevent and address bullying. A qualitative research design was employed, with data collected through interviews, observations, and document analysis involving the principal, teachers, students, and the CFS team. The findings indicate that the school has implemented comprehensive bullying prevention measures, including needs-based planning, integration of character-building activities, active involvement of stakeholders, and the use of technology such as the Si Galing application for anonymous reporting. The study also found a significant reduction in bullying incidents and improvements in students' sense of safety, emotional well-being, and participation in school activities. In conclusion, the research highlights that successful child-friendly school management requires thorough planning, collaborative execution, and continuous evaluation to ensure sustainable bullying prevention efforts in elementary schools.